The Global Publication Output in Augmented Reality Research: A Scientometric Assessment for 1992-2019 - Gupta, B. M.; Dhawan, S. M.; Rao, I.K. Ravichandra (International Journal of Knowledge Content Development & Technology, 2020)
The paper summarizes Augment Reality research output, using data from the Scopus database covering the 22 years period 1996-2017. During this time, AR researchers created a total of 15425 publications registered a high of 25% growth per annum and averaging 8.4 citations per paper. Less than 1% of the global output in the subject appeared as highly cited papers with over 100 citations per paper. The study identified 20 most productive organizations, authors and journals in AR research. The top 10 countries that dominate the field account for 74% of the global publications share with the USA accounting for the highest percentage (18.8%) and the U.K. leading in relative citation index (2.13). International collaboration has been a major driver of research in the subject with between; 13% to 42% of AR research output of the top 10 countries involving international collaborators. Computer Science is one of the most popular areas of research in AR research with other popular areas being Engineering, Mathematics and Social Sciences. <table class="MsoNormalTable" style="border-collapse: collapse; border: none; mso-border-alt: solid black .25pt; mso-table-overlap: never; mso-yfti-tbllook: 1184; margin-left: -2.25pt; margin-right: -2.25pt; mso-table-anchor-vertical: paragraph; mso-table-anchor-horizontal: column; mso-table-left: center; mso-table-top: top;" border="1" cellspacing="0" cellpadding="0" align="left"> <td style="width: 273.6pt; border-top: solid #828282 1.0pt; border-left: none; border-bottom: solid black 1.0pt; border-right: none; mso-border-top-alt: solid #828282 .25pt; mso-border-bottom-alt: solid black .25pt; padding: 5.65pt 1.4pt 5.65pt 1.4pt; height: 52.15pt;" valign="top" width="365"><p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; vertical-align: baseline; mso-element: frame; mso-element-wrap: around; mso-element-anchor-vertical: paragraph; mso-element-anchor-horizontal: column; mso-element-left: center; mso-element-top: top; mso-height-rule: exactly;">The paper summarizes Augment Reality research output, using data from the Scopus database covering the 22 years period 1996-2017. During this time, AR researchers created a total of 15425 publications registered a high of 25% growth per annum and averaging 8.4 citations per paper. Less than 1% of the global output in the subject appeared as highly cited papers with over 100 citations per paper. The study identified 20 most productive organizations, authors and journals in AR research. The top 10 countries that dominate the field account for 74% of the global publications share with the USA accounting for the highest percentage (18.8%) and the U.K. leading in relative citation index (2.13). International collaboration has been a major driver of research in the subject with between; 13% to 42% of AR research output of the top 10 countries involving international collaborators. Computer Science is one of the most popular areas of research in AR research with other popular areas being Engineering, Mathematics and Social Sciences. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; vertical-align: baseline; mso-element: frame; mso-element-wrap: around; mso-element-anchor-vertical: paragraph; mso-element-anchor-horizontal: column; mso-element-left: center; mso-element-top: top; mso-height-rule: exactly;">URL: http://ijkcdt.net/xml/24239/24239.pdf